PURLs: Yeast infection in pregnancy? Think twice about fluconazole - Barzin, Amir (J Fam Pract, 2016)
This study’s findings regarding the risk of miscarriage may mean it’s time to forego fluconazole in favor of topical azoles as first-line treatment.